Physiological responses during competition play of elite WNBL basketballers - Metcalfe, S.; Naughton, G.; Carlson, J. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Despite the increasing popularity of women`s basketball, very little research has investigated the physiological responses during competitive games. Sixteen players were selected from two Women`s National Basketball League (WNBL) teams on the basis of position. In the laboratory players completed a maximal incremental treadmill test, lactate profile assessment and were measured for anthropometric characteristics. No difference was observed in the sum of skinfolds and maximal effort data of the guards and forwards/centres. In addition to differences in height and body mass, the lactate profile test indicated an advantage in prolonged aerobic exercise in favour of the guards. Subjects were videotaped during competitive matches, with physiological responses of subjects analysed before, during, and after each game. Capillary fingertip blood samples were taken before the commencement of play, 10 minutes into the game, half-time, 10 minutes into the second half and three minutes after the completion of the match. Heart rate was monitored throughout the game. Changes in body mass were corrected for fluid consumption and used as an indicator of total body mass loss. The study indicated no difference for position in mean live playing time and total game heart rate values. In addition, no difference (p<0.05) was found in the absolute blood lactate concentrations of the guards and forwards/centres at similar stages in the game. The mean peak VO2 during treadmill testing was 48.88+ 1.18ml.kg-1min-1 and the mean peak heart rate was 193.43 + 2.56 b.min-1. Although the basketball matches were played under normal conditions (200C + 20C, 50% humidity) the calculated sweat loss was 1.1 + 0.1 litres per game. The mean overall heart rate during `live playing time` was 177.1 + 0.3 b.min-1 (91.3 + 0.4% HR max). The overall mean blood lactate concentration throughout the game was 5.7 mM indicating the involvement of glycolysis in the energy demands of the sport. It is concluded that the physiological requirements of elite female basketball are high, placing considerable demands on the cardiovascular and metabolic capacities of players.